Development of metal oxide nanoparticles with high stability against particle growth using a metastable solid solution - Leite, E. R.; Maciel, A. P.; Weber, I. T.; Lisboa-Filho, P. N.; Longo, E.; Paiva-Santos, C. O. [UNESP]; Andrade, A. V.C. [UNESP]; Pakoscimas, C. A. [UNESP]; Maniette, Y. [UNESP]; Schreiner, W. H. (My University, 2002)
Nanometer-size tin oxide particles with high thermal stability against particle growth below 900°C were synthesized. Low particle growth rate was achieved by doping SnO2 particles with rare earth ions during synthesis. Foreign cations moved to the particle surface, decreasing particle growth velocity. Furthermore, the addition of dopant allowed for the control of the initial particle size.